The Concept Of Maslahah By Al-Imam Malik And Al-Imam Al-Tufi - -, Nasiri; Ulum, Miftahul (Veteran Law Review, 2019)
Among the sources of Islamic law which is still disputed by Scholars argument is maslahah.  Some scholars reject it, but most agree to make maslahah as one of the sources of Islamic law in matters of ijtihad. Imam Malik considered as a Pioneer Scholar who makes maslahah as one source of his law ijtihad. His view was followed by the other Scholars, one of whom is Najm al-Din al-Tufi, acleric' Hambali.  However, the two leaders of thought are not the same, even in certain cases the difference is very sharp, although in certain parts have in common. In the view of Malik, maslahah serve as a source of  Islamic law in matters which are not discussed formally by nas and ijma ', but must not conflict with the spirit of the passage as a whole. In contrast, al-Tufi used maslahah both in matters discussed by nas/ijma’ or not. As for the area of applying maslahah, both agree that maslahah is only used in the matter of mu'amalah.